Penguatan Perilaku Pasien Rehabilitasi Mental Melalui Group Therapy Tentang Bahaya dan Dampak Merokok - Iqbal S, Muhammad; Jubir; Fauziah; Masthura, Syarifah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The issue of mental health has become a global concern, including in Indonesia. In 2022, according to the World Health Organization, there were 24 million cases of schizophrenia globally, with a prevalence rate of 7% in Indonesia. The primary focus of schizophrenia treatment involves antipsychotic medication therapy and mental rehabilitation. Individuals with schizophrenia often undergo perceptual changes due to smoking behavior. Method: This community service activity took place on October 28, 2023, involving the formation of a group therapy as a mental health support group. Education was provided through a method involving lectures and simulations through demonstration. This activity was attended by 19 individuals, consisting of 12 patients, 1 speaker, 1 leader, 9 facilitators, 1 minute-taker, the head of the room, and 4 room nurses. The socialization activity took place for 55 minutes. Results: Findings from the identification indicate that 30% of active smokers among the patients prefer kretek cigarettes. Additionally, 85% of the patients experience lip irritation, and 80% exhibit yellowing of the skin and fingernails due to smoking. After conducting pre-test and post-test activities, there was an increase in participants' knowledge about the understanding of the dangers and impacts of smoking, rising from 33% to 92%. Additionally, the attitude towards quitting smoking increased from 17% to 83%. Conclusion: The increase in knowledge and attitude among participants was observed through the formation of group therapy focusing on the dangers and impacts of smoking during mental rehabilitation.